Introducing the ARC technique (ask, record and confirm) for focus groups to validate qualitative data on a new business model for affordable housing in Malaysia - Mohd Noor, Mohd Zairul (IOP Publishing, 2019)
The ARC technique (ask, record and confirm) is introduced to perform validation and member verification procedures for focus-group data in real-time. During the focus-group sessions, response keywords were initially recorded on Post-it notes and were then pasted as a category onto an A1-sized sheet of paper. To illustrate the nature of the ARC technique, several steps were taken during the focus group and post-focus groups using this method to gauge feedback on the proposed business model (BM) of affordable housing. Next, the retrieved information was transferred into ATLAS.ti 7 for coding analysis and to generate meaning from the transcription. This paper is concluded with a discussion concerning the advantages and disadvantages of using the ARC technique for future studies.